Peran Layanan Bimbingan dan Konseling di Sekolah dalam Internalisasi Pendidikan Karakter Bangsa - Edi Kurnanto (PSGA LP2M IAIN Pontianak, 2015)
The character development should involve all parties in education world; the decision maker, the education expert, dan specifically the education doer such as school counsellor or teacher of Bimbingan dan Konseling. The counsellor involvement on character building is a must, since basically the character development is predominantly the counsellor’s expertise.